Administrative Means for the Protection of Plant and Animal Wealth in the Context of Biological Diversity - Snouci, Ali (Journal of Legal Studies and Researches, 2022)
This research aims to show that the protection of biodiversity. That affects the integrity of biological resources, which resulted in a collision between two objectives, namely the pursuit to ensure the balance of the environmental entity and the preservation of biodiversity in order to achieve sustainable development. The environment in general and reduce it from corrosion.